Variation In Some Promising Selections Of Wild Pomegranate (Punica Granatum L.) In Central Kashmir (Applied Biological Research, 2012)
The present study was aimed to document the genetic variability  in wild genotypes of pomegranate in central Kashmir. On the  basis of morphological and physicochemical characters, 33 genotypes were identified during intensive survey in districts Srinagar, Ganderbal and Budgam in 2009-2010. Remarkable  variability was observed amongst the genotypes for traits like plant height, plantspread, yield, fruit length, diameter and weight,  total aril weight, rind thickness, TSS, juice content, acidity, ascorbic acid, reducing sugars, total sugar and anthocyanin  contents. On the basis of yield and quality, 7 best genotypes were  selected for use in future pomegranate improvement programme.
Keywords: Genotype evaluation; Kashmir; pomegranate; selection; variability